Self-powered flexible touch sensors based on PZT thin films using laser lift-off - Noh, Myoung-Sub; Kim, Sangtae; Hwang, Do-Kyung; Kang, Chong-Yun (Elsevier BV, 2017)
Touch screens have become an inherent part of the user interface in many electronics applications such as smartphones. The two types of developed touch sensors, the resistive and capacitive sensing devices, may face several difficulties when applied to flexible device applications such as touch signals arising from bending motions. In this study, we assess the feasibility of flexible touch sensors based on piezoelectric PbZr0.52Ti0.48O3 (PZT) thin films. Piezoelectric ceramic based flexible touch sensors possess unique advantages including scalable fabrication, fast response time, durability, and being self-powered. A demonstration device has been fabricated with a sandwich structure consisting of Pt electrode/functional PZT/Pt electrode/flexible substrate structure using laser lift-off (LLO) method. In order to anneal the functional PZT layer at high temperature (600 °C), the device was first fabricated on the sapphire substrate and transferred via melting sacrificial PZT layer with an excimer laser. We demonstrate the detection of x- and y-axis touch location via piezoelectric materials and confirm that the flexible piezoelectric touch sensors can distinguish between touch-induced and bending-induced signals via signal location, signal shape, and duration time. A notable feature of this fabrication technique involves its possibility to be fabricated in high resolution. This device may potentially achieve high resolution with suitable fabrication techniques, thus, providing the possibility for the next generation touch sensors.